Enveloping analysis of data from educational platforms by area of knowledge - Eva Grissel Castro Coria; Rodrigo Gómez Monge (Universidad de Guadalajara, 2022)
In the presence of the pandemic caused by covid-19, digital platforms were implemented to continue with the education processes from isolation. In the case of higher education that imparts various areas of knowledge, different results were identified in the use of the same digital platforms. In response to this, it was necessary to analyze how the technological characteristics implemented at a higher level in Mexico have influenced the participation, attendance and evaluation of students by area of knowledge. Therefore, a data envelopment analysis was performed to measure the efficiency of the inputs and outputs described by the literature; the limitations of the research was circumscribed by the amount of data to be analyzed. As a result, it was identified that the greater the number of features added to the digital platforms, the better levels of participation, attendance and evaluation of students by academic area. Likewise, when considering future lines of research, it is considered ideal to elaborate on the various methods of digital evaluation, such as the digital portfolio and feedback.